Impact of middle-of-the-night awakenings on health status, activity impairment, and costs - Moline M (Dove Medical Press, 2014)
Margaret Moline,1 Marco daCosta DiBonaventura,2 Dhvani Shah,1 Rami Ben-Joseph1 1Purdue Pharma, LP, Stamford, CT, USA; 2Health Outcomes Practice, Kantar Health, New York, NY, USA Study objectives: Middle-of-the-night (MOTN) awakenings with difficulty returning to sleep are among the most common symptoms of insomnia. Despite the epidemiological studies that have been conducted, there is a lack of data on the impact of MOTN awakenings on health status and socioeconomic indicators in comparison with other insomnia symptoms. Methods: Data were analyzed from the 2011 US National Health and Wellness Survey (adults ≥18 years old; N=60,783), which asked respondents whether they had experienced specific symptoms of insomnia (ie, MOTN awakenings, difficulty falling asleep, waking several times, waking up too early, or poor quality of sleep). Respondents who reported only one insomnia symptom were compared among insomnia subgroups and with no insomnia symptom controls with respect to demographics, health history, and health outcomes (Short Form-12v2, Work Productivity and Activity Impairment questionnaire, and costs). Additional analyses compared respondents with only MOTN awakenings and matched controls on health outcomes. Results: MOTN awakenings without other insomnia symptoms were reported by 3.5% of respondents. Poor quality of sleep was associated with the strongest effects on health status compared with other insomnia symptoms even after adjusting for demographic and health characteristics differences. Differences across insomnia symptoms with respect to cost-related outcomes were generally modest, though all were higher (if not significantly so) than respondents without insomnia. Respondents who experienced only waking several times and only MOTN awakenings had the highest direct costs, while respondents who experienced only poor quality of sleep and only difficulty falling asleep had the highest indirect costs. Respondents with only MOTN awakenings reported significantly worse mental and physical health status and worse health utilities relative to insomnia-free matched controls (all P<0.05). Annual per-employee indirect costs were also significantly higher ($4,328 vs $3,000; P<0.05). Among only MOTN awakenings respondents, 74.6% were considered only symptomatic (ie, they did not report having insomnia or having been diagnosed with insomnia). Conclusion: These findings collectively highlight the prevalence and socioeconomic impact of specific types of insomnia symptoms, including MOTN awakenings, experienced by adults in the US. Keywords: insomnia, nocturnal awakenings, work productivity, health outcomes, sleep quality, sleep symptoms